BELAJAR JADI PEMIMPIN MELALUI BUKU KAS PENGENALAN AKUNTANSI SEDERHANA UNTUK SANTRI USIA DINI - Anggraini, Anggun; Indawati, Indawati; Sunarto, Ading (Yayasan Education and Social Center, 2026)
This community service program was carried out at Pesantren Tahfidz RH La Tahzan, targeting early-age santri (students). The main objective was to equip them with basic leadership skills through the introduction of simple accounting using a Cash Book. The santri were introduced to easy-to-understand financial recording concepts, enabling them to manage small activities independently and responsibly. The implementation methods included lectures, hands-on practice in recording simple transactions, and group simulations of cash management. The results showed that the santri not only understood the fundamentals of accounting but also began to develop discipline, transparency, and responsibility as future leaders. This program is expected to serve as an initial step in shaping leadership character based on financial literacy within the pesantren environment, while also contributing to strengthening non-formal education relevant to the santri’s future needs.